Modular Evaluation of Key Components of User Experience Indrive Application - Kennesty Ayustia Darmawan; Dwi Fatrianto Suyatno (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2026)
The InDrive application is an online transportation service that utilizes a fare negotiation system between users and drivers. In the highly competitive online transportation industry, user experience has become an important aspect that must be considered. This study aims to identify and analyze the user experience of the InDrive application using the Modular Evaluation of Key Components of User Experience (meCUE) 2.0 method with a quantitative descriptive approach. Research data were collected through the distribution of questionnaires to 170 active InDrive users in Indonesia using a purposive sampling technique. The questionnaire was structured based on the five modules of meCUE 2.0 and analyzed using descriptive statistical methods. The results indicate that the usefulness and usability aspects are categorized as high, while visual appearance, emotional reactions, as well as users’ intention to use and loyalty are categorized as moderate to fairly good. Overall, the user experience of the InDrive application is evaluated positively; however, improvements are still needed in several aspects to further enhance service quality.